Anesthesia interventions that alter perioperative mortality: a scoping review - Boet, Sylvain; Etherington, Nicole; Nicola, David; Beck, Andrew; Bragg, Susan; Carrigan, Ian D; Larrigan, Sarah; Mendonca, Cassandra T; Miao, Isaac; Postonogova, Tatyana; Walker, Benjamin; De Wit, José; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background With over 230 million surgical procedures performed annually worldwide, better application of evidence in anesthesia and perioperative medicine may reduce widespread variation in clinical practice and improve patient care. However, a comprehensive summary of the complete available evidence has yet to be conducted. This scoping review aims to map the existing literature investigating perioperative anesthesia interventions and their potential impact on patient mortality, to inform future knowledge translation and ultimately improve perioperative clinical practice. Methods Searches were conducted in MEDLINE, EMBASE, CINAHL, and the Cochrane Library databases from inception to March 2015. Study inclusion criteria were adult patients, surgical procedures requiring anesthesia, perioperative intervention conducted/organized by a professional with training in anesthesia, randomized controlled trials (RCTs), and patient mortality as an outcome. Studies were screened for inclusion, and data was extracted in duplicate by pairs of independent reviewers. Data were extracted, tabulated, and reported thematically. Results Among the 10,505 publications identified, 369 RCTs (n = 147,326 patients) met the eligibility criteria. While 15 intervention themes were identified, only 7 themes (39 studies) had a significant impact on mortality: pharmacotherapy (n = 23), nutritional (n = 3), transfusion (n = 4), ventilation (n = 5), glucose control (n = 1), medical device (n = 2), and dialysis (n = 1). Conclusions By mapping intervention themes, this scoping review has identified areas requiring further systematic investigation given their potential value for reducing patient mortality as well as areas where continued investment may not be cost-effective given limited evidence for improving survival. This is a key starting point for future knowledge translation to optimize anesthesia practice.